GRAFIK FRY DALAM MENGUKUR KETERBACAAN WACANA BUKU TEMATIK KELAS IV SEKOLAH DASAR - Feby Inggriyani; Dindin MZM; Milhamdan Gunawan; Azis Lukman Praja (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to measure the level of readability of discourse in 2013 thematic books for grade IV SD semester 1 revision 2018 in order to determine whether it is appropriate or not with the grade level. The method used in this study is a qualitative descriptive method. The data used is in the form of discourse texts in the 2013 curriculum thematic book for grade IV SD semester 1 revision 2018 published by the Ministry of Education and Culture. The technique used in this study is a data analysis technique, where the data source becomes a reference for clear mapping so that the calculation results can be measured and the level of readability is determined using the fry chart steps. The results of this study indicate that from 15 samples of discourse as data analyzed for their readability, it can be concluded that the readability level of the thematic books of the 2013 curriculum for fourth grade elementary school semester 1 revision 2018 using a fry chart consisting of five themes obtained the following results: Thematic Book Theme 1 The Beauty of Togetherness obtained readability results for grades 6, 7, and 8 so that it was not suitable for fourth grade elementary school students. Thematic Book Theme 2 Always Save Energy obtained readability results for grades 8, 9, and 10 so it was not suitable for fourth grade elementary school students. Thematic Book Theme 3 Caring for Living Creatures has a readability level for grades 6, 7, and 8 so it is not suitable for fourth grade elementary school students. Thematic Books Theme 4 Various Jobs obtained readability results for grades 4,5, and 6 so that they were suitable for fourth grade elementary school students. Theme 5 My Heroes obtained readability results for grades 8, 9, and 10 so it was not suitable for fourth grade elementary school students.